Analysis of the Relationship of Stigma to the Quality Life of Leprosy Patients - Ariesty Ajsal, Andi Ayu; Rahmawati, Rahmawati (Hasanuddin Medan, 2023)
Leprosy sufferers from a very high disease burden, those with disabilities become unproductive, unable to live independently to meet their needs. WHO defines quality of life as an individual's sense of their place in life within the framework of their culture, value system, and its link to life objectives, expectations, standards, and other relevant factors. Stigma against leprosy sufferers and even their entire families is still found in society. This is what makes most leprosy sufferers prefer to keep to themselves and avoid association with society because they are ashamed and afraid of their illness. So that it can affect the quality of life. Therefore, this study was conducted to analyze the relationship between stigma and quality of life. This study used primary data through interviews with 63 lepers with a cross-sectional study design using WHOQOL-BREF. The results of this study indicate that there is a relationship between stigma and quality of life for leprosy sufferers in Bone district with a p value = 0.000 < 0.05.